The Effects of Lifestyle and Financial Literacy on Student Consumptive Behavior (Case Study of Students of the Department of Social Sciences, Faculty of Teacher Training and Education, University of Lambung Mangkurat Banjarmasin). - Annisa Annisa; Monry Fraick Nicky Gillian Ratumbuysang; Maulana Rizky; Baseran Nor (Diversity: Jurnal Ilmiah Pascasarjana, 2023)
This study aims to analyze the effect of financial literacy and lifestyle on student consumptive behavior in KIP scholarship students class of 2021, Department of Social Sciences, Teaching and Education Faculty, Lambung Mangkurat University, Banjarmasin. Descriptive analysis using a quantitative approach is the research methodology used. 137 students made up the research subjects, Data analysis methods included multiple linear regression and descriptive analysis. Data was collected utilizing questionnaires and Google Forms for validity and reliability assessments. The findings indicated that student consumption behavior was positively and significantly influenced by financial literacy and lifestyle. It can be observed that the equation for multiple linear regression is Y = 25.088 + 0.117 X1 + 0.235 X2. A favorable and significant association between financial literacy and lifestyle and students' consumption behavior may be inferred from the hypothesis test. The computed F value is 6,988 > F table 0.159, and the significance value (Sig.) is known to be 0.001 0.05. Therefore, it can be inferred that there is a positive and significant relationship between financial literacy and lifestyle on the consumption behavior of students at Lambung Mangkurat University in Banjarmasin's Department of Social Sciences Keywords: Financial Literacy, Lifestyle, Consumptive Behavior